2017
DOI: 10.1055/s-0037-1600521
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Chromosomal Abnormalities in Products of Conception

Abstract: Purpose To describe the frequencies of chromosomal abnormalities found in abortion material, and to observe its correlation to maternal age. Methods A retrospective study was conducted based on data obtained from the databank of a medical genetics laboratory in Belo Horizonte, MG, Brazil. A total of 884 results from products of conception analysis were included, 204 of which were analyzed by cytogenetics, and 680 by molecular biology based on quantitative fluorescence polymerase chain reaction (QF-PCR). The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
12
0
5
Order By: Relevance
“…55 The other was conducted in 884 products of conception, 204 of which were analyzed by cytogenetics and 680 by molecular biology based on QF-PCR. 56 Despite using different techniques, the abnormal results were similar (40% by QF-PCR and 48% by cytogenetics). 56 A recent study, using only conven-tional CA, with 457 products of conception showed that 382 cases were sucessfully karyotyped while 75 cases of cell culture failed (culture failure rate: 16.42%).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…55 The other was conducted in 884 products of conception, 204 of which were analyzed by cytogenetics and 680 by molecular biology based on QF-PCR. 56 Despite using different techniques, the abnormal results were similar (40% by QF-PCR and 48% by cytogenetics). 56 A recent study, using only conven-tional CA, with 457 products of conception showed that 382 cases were sucessfully karyotyped while 75 cases of cell culture failed (culture failure rate: 16.42%).…”
Section: Discussionmentioning
confidence: 93%
“…56 Despite using different techniques, the abnormal results were similar (40% by QF-PCR and 48% by cytogenetics). 56 A recent study, using only conven-tional CA, with 457 products of conception showed that 382 cases were sucessfully karyotyped while 75 cases of cell culture failed (culture failure rate: 16.42%). Cytogenetic abnormalities were detected in 127 of the 382 cases (33.24%).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations